Telehealth virtual reality intervention reduces chronic pain in a randomized crossover study - Luana Colloca; Anna Han; Rachel Massalee; Nandini Raghuraman; Rachel L. Cundiff-O’Sullivan; Giancarlo Colloca; Yang Wang (npj Digital Medicine)
Abstract The efficacy of telehealth Virtual Reality (VR) for chronic pain, a promising digital intervention, remains underexplored due to methodological challenges. In a 5-week crossover trial, we compared VR to matched audio content control in individuals with chronic pain. VR significantly reduced pain intensity, anxiety, and pain interference while improving mood and sleep quality. Findings highlight the potential of telehealth-based VR for addressing real-world challenges in managing chronic pain. ISRCTN12473220 (07/18/2023).